Kemas Ulang Informasi dalam Perspektif Budaya Informasi Digital - Adelia, Nisa (Jurnal Al- Ma'arif : Ilmu Perpustakaan dan Informasi Islam, 2022)
The development of information technology brings major changes in human life. This big change cannot be separated from the leap in television, internet, and mobile phone usage in a fairly short period of time. This has a logical consequence on the level of human consumption of information technology. The flexibility of information technology also allows anyone to produce information and disseminate it, resulting in a lot of information circulating in various forms and formats. One of the digital information production practices today is information repackaging. Several scientific journals have written about the good practice of repackaging information in one of the information institutions, namely the library. Various purposes of repackaging are presented, which in essence is the accessibility and dissemination of information itself. Repacking information means making information packaging from existing information. In order to meet the information needs that are still relevant to today's phenomena. The repackaging of information with these various purposes signifies the existence of a new culture in the concept of information in this digital era. Seeing the existence of a culture of disseminating information with the information repackaging method, this article analyzes the practice of repackaging information in the perspective of digital information culture from Treddinick (2008). Trddinick (2008) first looks at text values in the early development of texts associated with textual works where this helps stabilize their referential values, and then examines how digital technology changes that stability, and Treddinick (2008) looks at how originality, knowledge and the power of text in the digital age